Effects of happiness management and organisational justice on organisational commitment - Galván Vela, Esthela; Martínez Arvizu, Orlando Josué; Salazar-Altamirano, Mario Alberto; Ravina-Ripoll, Rafael (My University, 2026)
Purpose – The results confirm that Human Resource Practices (HRPs) positively influence both happiness management and brand pride, but not performance directly. In contrast, both happiness management and brand pride significantly affect job performance. Furthermore, a marginal mediation of happiness management is also observed in the relationship between HRPs and performance (p 5 0.051), which suggests a near-significant emotional mechanism. Significant mediations of brand pride and happiness management are also found between pride and performance. Design/methodology/approach – A quantitative cross-sectional design was employed with 408 participants. Data were analysed using covariance-based structural equation modelling (CB-SEM) to assess the direct and indirect relationships proposed in the theoretical model. Findings – The results reveal that happiness management is positively associated with both organisational justice and commitment, with justice partially mediating this relationship. Research limitations/implications – The cross-sectional design and non-probabilistic sampling restrict causal inference and generalisability. Future studies should employ longitudinal approaches and test moderators such as leadership style or perceived organisational support. Practical implications – The findings guide higher education leaders to implement emotional and psychological training programmes that foster happiness, fairness and commitment through transparent workload allocation, fair promotion systems and participatory decision-making. Social implications – Promoting organisational cultures grounded in happiness and justice strengthens equity, well-being and institutional resilience, contributing to the Sustainable Development Goals SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth). Originality/value – The study provides novel evidence in the Ibero-American context by integrating four constructs into a single explanatory model, extending social exchange theory from an emotional perspective. It highlights that happiness management constitutes a management strategy and an ethical and cultural responsibility for building more human and sustainable organisations. Practical implications include promoting emotionally intelligent communication,symbolic recognition practices and a culture thatfosters employee pride and well-being.
Journal of Management Development
Keywords: Happiness management; Organisational justice; Organisational commitment; Positive organisational behaviour; Campus Tijuana